EXPERIMENTAL REVIEW OF THE RUBBER PAD OF THE NEW DESIGN OF THE SEWING MACHINE - Bozorova, Farida; Djuraev , Anvar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Annotation. The scientific research illustrates that the results of experimental studies to determine the loading of the recommended design of the compound paws with a rubber shock absorber of the mechanism for moving materials in a sewing machine. Based on the analysis of the obtained oscillograms and the constructed graphical dependencies, the best parameters of the shock absorber and the compound paws of the sewing machine are recommended.